Anlotinib-induced renovascular hypertension and severe coronary artery stenosis: a case report and literature review - Xiao, Yao; Liu, Kai (Frontiers in Oncology, 2026)
Anlotinib is a multi-target tyrosine kinase inhibitor that has been approved in China as a third-line treatment for advanced non-small cell lung cancer. It exerts anti-tumor effects by inhibiting tumor growth and tumor angiogenesis, and its toxicity also arises from this mechanism. Anlotinib can damage vascular endothelium, thereby inducing cardiovascular toxicity, which leads to hypertension, hyperlipidemia, accelerated atherosclerosis, and the initiation of atherosclerotic cardiovascular disease, ultimately resulting in life-threatening cardiovascular events. To the best of our knowledge, this study is the first case report documenting the development of hypertension, hyperlipidemia, hypothyroidism, subsequent discovery of bilateral renal artery stenosis, and acute myocardial infarction in a young patient receiving anlotinib treatment. This showed anlotinib may accelerate systemic large/medium-sized artery atherosclerosis in the context of complex tumor therapy, causing life-threatening cardiovascular events. Besides, it highlights the necessity of regular monitoring of relevant indicators during follow-up for patients undergoing anlotinib therapy, enabling early detection of warning signs and timely intervention.